Penghematan Air Irigasi Saat Olah Tanah dengan Tanaman Sela pada Subak - Tika, I Wayan; Madrini, Ida Ayu Gede Bintang; Sumiyati, Sumiyati; Sulastri, Ni Nyoman (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 5 No 2 (2020), 2020)
One of the significant programs in paddy rice cultivation is the management of irrigation water efficiently and effectively. Commonly, the planting schedule for the subak system in Bali is performed simultaneously, which leads to the highest peak of irrigation water demand. The high demand for water causes a high risk of water shortage, especially during soil tillage. One of the solutions to save irrigation water is to use the intercropping farming method. This method allows farmers to cultivate more than a single crop in a given field area (Monoculture). Based on recent field observation, approximately 10% of the rice paddy field was chili pepper field as a second crop for the intercropping farming method. The result shows by using the intercropping farming method; the water-saving was not significant, which is less than 7 %.  It is important to note that the data was collected during the chili pepper growing season from July to August. Additionally, during that time, the soil tillage period was quite long, which was 50 days.